Calcium rich food wastes based catalysts for biodiesel production - Catarino, Maria Alice (2017)
Biodiesel produced from food wastes can help to solve several environmental issues: anthropogenic carbon emissions due to fossil fuels combustion and waste management. Biodiesel was produced using waste frying oils (WFO) and calcium rich food wastes such as mollusk, shrimp, eggs shells and cuttlebone to produce calcium based heterogeneous catalysts by calcination. The characterization of chalky white calcined powders by XRD showed diffraction lines typical of lime but some samples were slightly contaminated with calcite. The powders with low crystallinity showed high hydration rate presenting XRD features ascribable to nanocrystals of calcium hydroxide. The post reaction samples presented mainly lines due to calcium diglyceroxide and methoxide. Thermograms of used catalysts showed some weight loss of these calcium compounds, confirming the presence of such phases. All prepared catalysts were effective in catalyzing the methanolysis of soybean oil. A FAME yield around 96% was obtained after 2.5 h of reaction. When using WFO, the FAME yield was only 65% with simultaneous production of soap. The use of WFO and soybean oil mixtures attenuates the loss of catalytic performances. The obtained glycerin's presented a light color characteristic of heterogeneous catalyzed processes. FTIR spectra of glycerin's showed some features belonging to matter organic non glycerin and methanol. The catalyst reutilization without intermediate reactivation indicated that catalysts are somewhat stable. When WFO was used, the reused catalysts showed improved performance probably due to the formation of calcium diglyceroxide. Nevertheless, calcium diglyceroxide is bound to promote homogeneous catalysis and consequent deactivation.